Perfil de conocimiento financiero y edad en estudiantes de bachillerato de instituciones del sistema privado - Jaramillo Veintimilla, Nubia Johanna (2023)
Nowadays, financial education is an essential factor in the training of people. In addition to achieving a certain level of well-being, it helps to build advantageous knowledge in the context in which we live. Since this entails new responsibilities, challenges, and financial dangers, which, if not faced with all the tools available, could deteriorate the quality of life, financial education has become very relevant, especially for the youngest. One of the reasons is that the lessons taught at that age are usually enduring and generate better financial habits. The main interest of the research was to evaluate the relationship between financial education and age in students from private educational centers. A survey was applied, with a sample of 302 students, from 4 private schools in Loja city. The students were chosen for convenience, ranging from 14 to 18 years old teens. The results showed no relationship between age and level of financial knowledge since this confirms Piaget's theory that young people at this age are already in a position to form structured and analytical expertise. Therefore, the ability or lack of it will clearly depend on their willingness to learn and the quality of the teaching given to them, concluding that the level of general knowledge obtained is medium-high (level 4).